A comparison of the bacteria at Bakoven Bay and Hottentotshuisie as indicators of marine pollution from a sewage outfall - Breyer-Menke, Carel Jan (Department of Environmental and Geographical Science, 2023)
A comparison is made of the bacterial populations at two geographically similar near-shore marine sites. The difference between the sites is that one is influenced by a raw sewage outfall. Sea water samples were drawn directly by means of a handheld all-glass bacteriological sampling device. Sea-water samples were analysed for a total coliform count, presumptive E. coli type I and a total bacterial count on a marine agar medium. A proportion of the isolates on the total count plates were subjected to a number of physical, biochemical and antibiotic tests and classified into genera. Bacteriological differences between the sites were shown by the coliform tests. Total count isolates and in particular the pseudomonads also showed bacteriological differences between the sites. It is indicated that these organisms could possibly be used to demonstrate stressed conditions in near-shore marine environments resulting from sources other than sewage contamination.